Fabrication of calixarene films using Langmuir and Langmuir-Blodgett (LB) method for heavy metal ion sensing (IR) - Noor Azyyati Noor Azahari (2014)
This study aims to develop novel calixarenes monolayer and multilayer films for sensing properties of heavy metals ion, namely Pb2+ and Cd2+, using Langmuir and Langmuir-Blodgett (LB) films techniques. Langmuir monolayer formation at the air-water interface was achieved by spreading amphiphilic molecules on water subphase and compressing them into an ordered arrangement. LB films were formed by transferring the floating monolayer molecules at the air-water interface onto a solid substrate. The properties of the calixarenes molecules developed from Langmuir film were discussed on terms of surface pressure-area (?-A) isotherms, surface potential (V) and effective dipole moment (?) of the molecules in the absence and presence of metal ions. The calixarenes LB films were characterized by UV-visible spectroscopy to identify their optical properties. FTIR analysis yielded useful information regarding the specific interactions of calixarenes and the tested metal ions. Under the optimum experimental conditions, the lowest detectable concentration of Pb2+ is 2.5x10-2 mM and Cd2+ is 5.0x10-2 mM. Furthermore, calixarenes showed a well-defined response towards the Pb2+ and Cd2+ with good sensitivity and reproducibility. The detection mechanism of calixarenes with Pb2+ and Cd2+ ions in aqueous solution were also discussed. These findings are suitable to be applied for the development of optical sensors for the detection of heavy metal pollution in water